Socio-economic impacts of typhoon Haiyan (Yolanda) in the coastal barangays of the Municipality of Laua-an, Antique a valuation of damage, preparedness, response and recovery. - Dominguez, Lyrin Mae M.
This study focuses on the measures undertaken and costs incurred by coastal households and LGU in preparing on, responding to and recovering from Typhoon Haiyan. Data were gathered through a household survey of 156 selected households in all coastal barangays of the Municipality of Laua-an. Key informant interviews were also conducted to support survey of the data. The five priorities of action of the Hyogo Framework for Action were used to explain the measures undertaken by the LGU for typhoon Haiyan. Replacement cost, defensive expenditures and market price method were utilized to determine the costs of damages and losses including Disaster Risk Reduction (DRR) measures undertaken by the LGU and coastal households. The result of the study showed that the highest cost was incurred by the economic sector. The LGU spent only .68 percent in preparedness measures. The biggest damage in terms of cost was experienced by the economic sector. The coastal household incurred the biggest damage cost on their houses. This is even higher than the total amount they spent on DRR measures. The study recommends improvements of DRRM programs to enhance resiliency for future disasters.